2009
DOI: 10.1021/jf9024079
|View full text |Cite
|
Sign up to set email alerts
|

Nondigestible Saccharides Suppress the Bacterial Degradation of Quercetin Aglycone in the Large Intestine and Enhance the Bioavailability of Quercetin Glucoside in Rats

Abstract: Contribution of intestinal bacterial degradation of quercetin aglycone to the promotive effects of fructooligosaccharides and di-D-fructose anhydride III (DFAIII) on quercetin-3-O-beta-glucoside (Q3G) bioavailability was examined. Male Sprague-Dawley rats were fed 0.68% Q3G diets with or without 1.5% or 3% oligosaccharides for 2 weeks. Blood levels and urinary excretion of quercetin and methylquercetin conjugates, measured by methanol extraction and LC-MS analyses, were dose-dependently and adaptively increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…It is widely acknowledged that the degradation of flavonoid in the gut is the important factor influencing its bioavailability [10]. Herein, we employed UPLC-qTOF/MS to determinate genistein aglycone and its gut microorganism-based characteristic metabolite (DH-GEN) in feces in order to indirectly evaluate the stability of genistein in the gut.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is widely acknowledged that the degradation of flavonoid in the gut is the important factor influencing its bioavailability [10]. Herein, we employed UPLC-qTOF/MS to determinate genistein aglycone and its gut microorganism-based characteristic metabolite (DH-GEN) in feces in order to indirectly evaluate the stability of genistein in the gut.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the possible potential mechanism was associated with the inhibition of non-digestible oligosaccharides against the bacterial degradation of quercetin aglycone in the intestine [10], but this effect has not yet been confirmed by analysis of the microbial characteristic metabolites of flavonoids. In the present study, the DH-GEN was found to be a characteristic metabolite of genistein degraded by intestinal microflora, and its feces excretion of the tested mice in the co-treatment groups was also decreased with the increased doses of simultaneous ingested stachyose (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that plasma polyphenol concentrations are no more than~5 μM following oral consumption, but the luminal concentrations are known to reach a much higher level. Matsukawa et al have reported that the quercetin concentration reached 300 μM in the cecum of rats fed a diet containing 0.68% quercetin glucoside (Matsukawa et al, 2009). This evidence suggests that the transcriptional regulation of claudin-4 by quercetin, leading to the promotion of barrier integrity, could be translated to in vivo applications.…”
Section: Discussionmentioning
confidence: 99%